Determinan Pengungkapan Laporan Berkelanjutan - Alvina Damayanti; Pancawati Hardiningsih (Jurnal Akuntansi dan Pajak, 2021)
This study aims to examine the effect of financial performance and firm size on the disclosure of sustainability reports with good corporate governance as a moderator. The population in this study are state-owned companies listed on the Indonesia Stock Exchange in 2015-2020. The sampling method used is purposive sampling as many as 54 state-owned companies. The analysis technique uses multiple linear analysis. The results showed that profitability, leverage and good corporate governance had no effect on the disclosure of the sustainability report. Company size has a negative effect on the disclosure of sustainability reports. Good corporate governance is not able to moderate the effect of profitability on the disclosure of the sustainability report. On the other hand, good corporate governance weakens the effect of leverage and good corporate governance strengthens company size on the disclosure of sustainability reports.